Prostate cancer cell-derived exosomal IL-8 fosters immune evasion by disturbing glucolipid metabolism of CD8+ T cell - Fan Xu; Xiumei Wang; Ying Huang; Xiaoqian Zhang; Wenbo Sun; Yuanyuan Du; Zhi Xu; Hengyuan Kou; Shuyi Zhu; Caidong Liu; Xiaowei Wei; Xiao Li; et al. (Cell Reports, 2023)
Summary: Depletion of CD8+ T cells is a major obstacle in immunotherapy; however, the relevant mechanisms remain largely unknown. Here, we showed that prostate cancer (PCa) cell-derived exosomes hamper CD8+ T cell function by transporting interleukin-8 (IL-8). Compared to the low IL-8 levels detected in immune cells, PCa cells secreted the abundance of IL-8 and further accumulated in exosomes. The delivery of PCa cell-derived exosomes into CD8+ T cells exhausted the cells through enhanced starvation. Mechanistically, exosomal IL-8 overactivated PPARα in recipient cells, thereby decreasing glucose utilization by downregulating GLUT1 and HK2 but increasing fatty acid catabolism via upregulation of CPT1A and ACOX1. PPARα further activates uncoupling protein 1 (UCP1), leading to fatty acid catabolism for thermogenesis rather than ATP synthesis. Consequently, inhibition of PPARα and UCP1 restores CD8+ T cell proliferation by counteracting the effect of exosomal IL-8. This study revealed that the tumor exosome-activated IL-8-PPARα-UCP1 axis harms tumor-infiltrating CD8+ T cells by interfering with energy metabolism.